2023
DOI: 10.1101/2023.03.15.532836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bipartite invariance in mouse primary visual cortex

Abstract: A defining characteristic of intelligent systems, whether natural or artificial, is the ability to generalize and infer behaviorally relevant latent causes from high-dimensional sensory input, despite significant variations in the environment. To understand how brains achieve generalization, it is crucial to identify the features to which neurons respond selectively and invariantly. However, the high-dimensional nature of visual inputs, the non-linearity of information processing in the brain, and limited expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A remedy for this limitation is to search for diverse exciting inputs by generating stimuli that are both highly effective at eliciting neural responses and at the same time distinct from one another. Ding et al (49) used this approach to study bipartite invariance in mouse V1 (see also (50)). Related to this, Goldin et al (51) searched for locally optimal stimulus perturbations for mouse RGCs and found that the selectivity for positive or negative contrast in a subset of cells is context-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…A remedy for this limitation is to search for diverse exciting inputs by generating stimuli that are both highly effective at eliciting neural responses and at the same time distinct from one another. Ding et al (49) used this approach to study bipartite invariance in mouse V1 (see also (50)). Related to this, Goldin et al (51) searched for locally optimal stimulus perturbations for mouse RGCs and found that the selectivity for positive or negative contrast in a subset of cells is context-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…recurrence, top-down processing streams) that account for dynamical processing in the brain [ 59 ]. Moreover, our multi-task modeling approach, together with in-silico experimentation, promises to facilitate the generation of hypotheses about tuning directions via maximally exciting inputs (MEIs) [ 10 , 11 , 60 , 61 ], diverse exciting inputs (DEIs) [ 62 , 63 ], or controversial stimuli [ 49 ].…”
Section: Discussionmentioning
confidence: 99%